An Empirical Analysis of Oil Painting Techniques Under Opera Symbols - Zeng, Chuifa; Hermilinda Adas, Imelda (วารสารบัณฑิตศาส์น มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2024)
Chinese opera has a powerful and unique symbolic identity. This paper focuses on the symbolic symbols in the multiple and complex symbolic systems of the opera and uses its own creations as an example to start a discussion on the visual images. Through the system of meaning under symbolization and the extended transcendental value of the connotative meaning of the opera are reconstructed in the visual images, exploring the other side of human nature and forming an intricate and contradictory deconstruction body. Opera’s unique symbol system throughout the performance process of the opera, injecting new life into traditional Chinese culture, especially in the stage performance to strengthen the charm of opera, enriching the diversified and profound art theater.